Specific absorption rate distribution evaluation in a different substrate for hyperthermia treatment - Bibi Sarpinah Sh Naimullah; Kasumawati Lias; Norlida Buniyamin; Ahmad Tirmizi Jobli; Mazlina Mansor Hassan (Institute of Advanced Engineering and Science, 2022)
Hyperthermia treatment procedure (HTP) isatreatment that uses high heatgenerated from electromagnetic (EM) waves, which is about 42 °C to 45 °C within a particular duration. However, poor focus position distance on the treated tissue has become a significant concern among the researchers since it may contribute to a wide area of unwanted hot spots, which lead to severe adverse health effects on healthy tissue.This paper presents a specific absorption rate (SAR) distribution evaluation of different microstrip antenna substrates with different electrical permittivities, contributing to different sizes of microstrip antenna patches, which then provide different attainment of the SAR distribution on the treated tissue. Operating frequencies of 434MHz, 915 MHz, and 2,450 MHz with 10 W operating powerare utilized. ASEMCAD X is used to conduct a simulation in obtaining the SAR distribution, which determines the focus position distance on different tumour (malignant tissue) sizes. Based on the results, the suitable substrate for frequency 915 MHz and 2,450MHz is RT5880, and RT5870, while RO3210 and RT6010 performed their best at 434MHz and 2,450MHz. The finding of this study can be used for further research in optimizing microstrip antenna development for HTP.